Konflik Sako Adat Di Kinali Tahun 2017-2021 - Dicha Maulia Dani; Erniwati Erniwati (Jurnal Kronologi, 2023)
Abstract This research discusses the customary conflict in Kinali in fighting over the inheritance rights over the sako or customary title Yang Tuan Kinali in 2017-2021 between two parties from different tribes, namely Asrul from the Koto tribe and Mustika Yana from the Jambak tribe. The purpose of this research is to see why customary conflicts can occur and how the process of these conflicts occurs. This study uses the historical method with four stages including heuristics which are the stages of gathering sources or materials, source criticism, interpretation and historiography. The results of this study indicate that the conflict over the traditional title of Yang Tuan Kinali that occurred between Asrul from the Koto Tribe and Mustika Yana from the Jambak Tribe was caused by Dutch interference in Dikinali customary leadership affairs in 1929 which disrupted the traditional leadership structure. The conflict that occurred in Kinali did not only involve two parties but also had an impact on the community. Keywords: Conflict, Leadership, Customs Abstrak Penelitian ini membahas tentang konflik adat di Kinali dalam memperebutkan hak waris atas sako atau gelar adat Yang Dipertuan Kinali pada tahun 2017-2021 antara dua pihak dari suku yang berbeda yaitu Asrul dari Suku Koto dan Mustika Yana dari Suku Jambak. Tujuan penelitian ini adalah untuk melihat mengapa konflik adat itu bisa terjadi dan bagaimana proses terjadinya konflik tersebut. Penelitian ini menggunakan metode sejarah dengan empat tahapan diantarannya heuristik yang merupakan tahapan pengumpulan sumber atau bahan, kritik sumber, interpretasi dan historiografi. Hasil penelitian ini menunjukan bahwa konflik perebutan gelar adat Yang Dipertuan Kinali yang terjadi antara Asrul dari Suku Koto dan Mustika Yana dari Suku Jambak diakari oleh adanya campur tangan Belanda dalam urusan kepemimpinan adat Dikinali tahun 1929 yang mengacaukan struktur kepemimpinan adat. Konflik yang terjadi di Kinali tidak hanya melibatkan dua pihak saja akan tetapi berdampak terhadap masyarakat.Kata Kunci: Konflik, Kepemimpinan, Adat